2006
DOI: 10.1177/095632020601700101
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of HIV-1 Replication by Oligonucleotide Analogues Directed to the Packaging Signal and Trans-Activating Response Region

Abstract: HIV possesses a remarkable capacity for mutational escape from therapeutics that target the viral proteins and enzymes. Inhibitory strategies aimed at highly conserved nucleic acid sequences within the genome are an attractive alternative. However, it has proven difficult to achieve an effective level of therapeutic at the appropriate site within the cell. Oligonucleotide delivery is a rapidly advancing field. We have investigated oligonucleotide analogues as steric-block therapeutics against two highly conser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

2007
2007
2009
2009

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 38 publications
2
10
0
Order By: Relevance
“…In earlier work, we showed that steric block antisense ONs composed of LNA/OMe mixmers directed to the trans-activation-responsive RNA TAR were very effective at blocking HIV-1 Tat-dependent trans-activation in a HeLa cell-based luciferase reporter model system when delivered by lipofection, and also showed antiviral activity (Arzumanov et al 2001;Turner et al 2005a;Brown et al 2006). These ON mixmers were designed to combine the very high binding affinity and biostability provided by LNA units together with the greater nuclease resistance and RNA binding strength of OMe nucleotides as compared with DNA.…”
Section: Introductionmentioning
confidence: 99%
“…In earlier work, we showed that steric block antisense ONs composed of LNA/OMe mixmers directed to the trans-activation-responsive RNA TAR were very effective at blocking HIV-1 Tat-dependent trans-activation in a HeLa cell-based luciferase reporter model system when delivered by lipofection, and also showed antiviral activity (Arzumanov et al 2001;Turner et al 2005a;Brown et al 2006). These ON mixmers were designed to combine the very high binding affinity and biostability provided by LNA units together with the greater nuclease resistance and RNA binding strength of OMe nucleotides as compared with DNA.…”
Section: Introductionmentioning
confidence: 99%
“…A little higher inhibitory activity was measured for 16-mer OMe/LNA mixmer 5 (40% at 1 µM), which is very similar to that obtained in an analogous anti-HIV-1 syncitia reduction assay for the same oligonucleotide from another recent study. [7] In conclusion, we have shown that a 16-mer all tricyclo-DNA oligonucleotide, targeted to the HIV-1 TAR region, similarly to 16 TAR OMe/LNA mixmer, blocks sequence-specific Tat-dependent trans-activation in Hela cells as well as HIV infectivity when delivered with cationic lipid. Thus, our study confirms that tricyclo-DNA oligonucleotides are promising antisense agents with potential for therapeutic applications.…”
Section: Resultsmentioning
confidence: 95%
“…[2−4] We found previously that a 16-mer OMe/LNA mixmer oligonucleotide complementary to TAR when delivered by cationic lipids effectively inhibited Tat-dependent trans-activation in a HeLa cell reporter assay [5,6] and syncitia formation induced by HIV-1 infection in HeLa T4 LTR cells. [7] Here we compare the trans-activation inhibitory activity of the 16-mer OMe/LNA mixmer with oligonucleotide analogs containing another type of conformationally restricted monomers-tricyclo-DNA. [8−11] …”
Section: Introductionmentioning
confidence: 99%
“…The ability of these ONs to inhibit Gag binding is also encouraging for these ONs to be investigated as molecular tools in cells or as anti-HIV therapeutics. [16,47] …”
Section: Discussionmentioning
confidence: 98%
“…[3,4] Steric-block ONs can block gene expression by inhibiting RNA-protein interactions during a number of cellular processes including RNA splicing, [5] translation, [6] and transcription [7][8][9][10][11][12] and have shown promise as therapeutics. [13][14][15][16][17] The sequence specific nature of steric-block ONs, and the ability to use very short ONs, suggests they have potential as in vitro tools for identifying specific RNA sequences involved in protein binding and for investigating the relative role of multiple binding sites.…”
Section: Introductionmentioning
confidence: 99%